Fossil woods with coniferalean affinities from the Upper Cretaceous (Campanian–Maastrichtian) Puntudo Chico Formation, Chubut Province, Argentina. (July 2019) - Vera, E.I.; Perez Loinaze, V.S.; Llorens, M.; Paez, M.; Passalia, M.G.
Abstract: The Puntudo Chico Formation is a continental sequence overlying the Chubut Group at the central-East of the Cañadón Asfalto Basin in Patagonia (Chubut Province, Argentina). The age of this unit, Campanian–Maastrichtian, makes it comparable with other Patagonian units, such as the Allen (Río Negro Province) and La Colonia Formation (Chubut Province), well-known by their paleontological content, including plants, mammals, and non-avian dinosaurs. Contrasting, the Puntudo Chico Formation fossil content is almost unknown, and even if fossil woods were reported, detailed studies were lacking. In this contribution, fossil woods collected from the Puntudo Chico Formation are studied, and three different conifer taxa are identified: Podocarpoxylon mazzonii (Petriella) Müller-Stoll & J. Schultze-Motel 1990, Brachyoxylon sp. cf. B. currumilii Bodnar, Escapa, Cúneo & Gnaedinger, 2013, and Agathoxylon antarcticus (Poole et Cantrill) Pujana, Santillana & Marenssi, 2014. This flora seems to be part of a distinctive Late Cretaceous–Danian floristic assemblages that inhabited a warm region located approximately at 38–42°S, that were probably linked and somewhat nearby the Kawas Sea, an inland sea that flooded the Neuquén and Río Colorado basins during the first Atlantic Transgressive Event in Patagonia. Highlights: Conifer woods are described from the Puntudo Chico Formation. Brachyoxylon, Agathoxylon and Podocarpoxylon are recognized. Similar floras are already reported from other Patagonian units. These floras probably grew near the Kawas Sea.